MODUS DORIAN: SEBUAH ALTERNATIF BAGI PENCIPTAAN HYMN - Daniel Sema (Sekolah Tinggi Theologia Abdiel, 2019)
In today's Indonesian churches there are two types of music in worship, namely: hymnal songs or hymn (which are still used in mainstream Protestant churches) and contemporary Christian songs (used in Pentecostal and Charismatic churches). Nevertheless, contemporary Christian singing began to be accepted by some Protestant Christians and its existence increasingly dominated and urged the hymn. In order for the hymn to not be easily abandoned and felt contemporary, the author offers a new alternative to the creation of the hymn that has based itself on the major-minor mode for centuries. The alternative is the use of church mode, namely the Dorian mode as the basis for the creation or arrangement of a hymn. For this reason, the author tries to present a hymn arrangement for the song